Textbooks as a Basic Resource for the Promotion of Intercultural Coexistence? A Case Study - Amante, Susana (2016)
It has become commonplace to assert that we are living in a time of rapid economic transformation and social mobilisation, which leads to a massive flow of people and goods across borders. This phenomenon has been changing the way in which communities function and, besides economic and social implications, political and cultural conditions follow a parallel course. No longer, if ever, can we speak of ‘pure’ cultures rooted in one particular geography, because cross-cultural interactions have been challenging one’s sense of identity. In fact, identities are hybrid, dynamic, often fractured and even imagined in nature. Yet, certain common experiences and phenotypical traits have contributed, most of the times, to the emergence of a national consciousness and to an ethnocentric/eurocentred vision of the world. Cliché as this may sound, since there is now a plethora of literature on multiculturalism and on interculturalism, the fact is that, in Portuguese schools, some students still seem to be shaped and limited by their cultural background and we, as teachers, need to prepare children for this contemporary globalised world. But education is much linked to the ideology of the ruling elites and is political at every stage. The textbook publishing industry, following a selective curriculum, is proof of the perpetuation of the status quo, because school materials have sometimes ignored and marginalised peoples seen as the ‘Other’. We, thus, intend to analyse the way textbooks have adopted and adapted to the government’s recent policies, the Common Core State Standards for Portuguese, namely in the treatment of a literary corpus. We will direct our attention to textbooks that address Mia Couto’s O Beijo da Palavrinha and O Gato e o Escuro to check if activities relating to these texts promote tolerance and acceptance of differences or if they are marked by ignorance and prejudice.